Introduction to Computing Using C++ and Object Technology - Ford H. William; Topp R. William (Prentice Hall, 1999)
An exciting new introductory C++ programming text for students and professionals interested in using objects and object-oriented design from the beginning. Introduction to Object Technology, Basic C++ Types and Programs, Describing and Declaring Classes, Basic C++ Control Structures, Developing Your Own Classes, Additional C++ Control Structures, Arrays, Program Design and Algorithms, Operator Overloading and Templates, Pointers and Dynamic Memory, Containers and Linked lists, Inheritance and Virtual Functions, Index.